Risk of dementia in older adults with low versus high occupation-based motivational processes: differential impact of frequency and proximity of social network. - Fankhauser, S.; Forstmeier, S.; Maercker, A.; Luppa, M.; Luck, T.; Riedel-Heller, S. G. (J Geriatr Psychiatry Neurol, 2015)
OBJECTIVES: This study investigates the impact of occupation-based motivational processes and social network variables on the incidence of dementia over 8 years. METHOD: Data were derived from the Leipzig Longitudinal Study of the Aged (LEILA75+), a population-based longitudinal study of individuals aged 75 years and older (n=1692 at baseline). Motivational processes were estimated based on the main occupation using the Occupational Information Network database. RESULTS: In a Cox proportional hazard model, motivational processes were not associated with the risk of dementia (hazard ratio [HR]: 0.93, 95% confidence interval [CI]: 0.74-1.16). Individuals with a higher frequency of social contact at baseline had a significantly lower risk of dementia (HR: 0.96, 95% CI: 0.91-0.99), while proximity of social contacts was not linked to the risk of dementia (HR: 1.03, 95% CI: 0.98-1.08). In individuals with low indices of motivational processes, the frequency of social contacts was associated with a lower risk of dementia (HR: 0.94, 95% CI: 0.88-1.00). On the other hand, proximity of social contacts was linked to a higher risk of dementia in individuals with high indices of motivational processes (HR: 1.09, 95% CI: 1.01-1.19). DISCUSSION: Results indicate that the frequency and proximity of social contacts have a differential impact on the risk of dementia according to lower or higher indices of motivational processes, while the impact of motivational processes on risk of dementia could not be confirmed. Future studies should carefully disentangle different aspects of social interactions and their association with motivational processes.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease/complications; Dementia/*epidemiology/*psychology; Disease Susceptibility; Female; Humans; Incidence; *Interpersonal Relations; Longitudinal Studies; Male; *Motivation; Occupations/*statistics & numerical data; Proportional Hazards Models; Risk; *Social Networking